TYPHOID (ILEAL) PERFORATION - Gul, M; Sajjad, A; Saeed, A.K. (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: One hundred and thirty cases over a period of five years are included in this study. Duration of the disease, duration of perforation, age, sex and various surgical treatments are analysed. Prognostic factors and causes of mortality and morbidity are discussed. Minimum surgical intervention is preferred, as mortality is increased in extensive surgical procedure, in already sick and toxic patients.